Evolution of anti-predator traits in response to a flexible targeting strategy by predators - Jackson, Andrew L (The Royal Society, 2006)
Anti-predator benefits increase with vigilance rate and group size in many species of animal, while simultaneously resource intake rates usually decrease. This implies that there is an optimal group size and vigilance rate that will maximize individual fitness. While this basic theory of vigilance has been modelled and tested extensively, it has often been assumed that the predator represents a ‘fixed-risk’ such that groups of prey are essentially independent entities that exert little or no effect on one another either directly or indirectly. We argue that this is an over-simplification, and propose that the behaviour of one group of prey will likely affect the fitness of another local group of prey if the predator preferentially attacks the most vulnerable group—rather than attack both with constant rates. Using a numerical simulation model, we make the first examination of this game and allow the prey to dynamically evolve both optimal group size distributions between two habitats and vigilance rates in response to a predator with a preference for whichever group is the more vulnerable. We show that the density of prey in the population and the sensitivity of a predator to differences in prey vulnerability are likely to drive the dynamics of such a game. This novel approach to vigilance theory opens the door to several challenging lines of future research, both experimental and theoretical.